2009
DOI: 10.1016/j.jmb.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma H2A Variants Reveal Novel Insights into Nucleosome Composition and Functions for this Histone Family

Abstract: Toxoplasma gondii is an obligate intracellular parasite. Toxoplasmosis is incurable because of its ability to differentiate from the rapidly replicating tachyzoite stage into a latent cyst form (bradyzoite stage). Gene regulation pertinent to Toxoplasma differentiation involves histone modification, but very little is known about the histone proteins in this early branching eukaryote. Here we report the characterization of three H2A histones, a canonical H2A1 and variants H2AX and H2AZ. H2AZ is the minor paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(142 citation statements)
references
References 50 publications
9
133
0
Order By: Relevance
“…H2AX is rapidly phosphorylated in response to double-stranded breaks (termed ␥H2AX), which are induced by MMS. We have established that Toxoplasma contains H2AX that becomes phosphorylated in response to double- stranded DNA breaks (12). In TgMYST-B-overexpressing parasites, however, we found high levels of basal ␥H2AX and found that the increase in ␥H2AX is dependent on the KAT activity of TgMYST-B (Fig.…”
Section: Tgmyst-b Protects Against Dna Damage Induced Bymentioning
confidence: 70%
See 1 more Smart Citation
“…H2AX is rapidly phosphorylated in response to double-stranded breaks (termed ␥H2AX), which are induced by MMS. We have established that Toxoplasma contains H2AX that becomes phosphorylated in response to double- stranded DNA breaks (12). In TgMYST-B-overexpressing parasites, however, we found high levels of basal ␥H2AX and found that the increase in ␥H2AX is dependent on the KAT activity of TgMYST-B (Fig.…”
Section: Tgmyst-b Protects Against Dna Damage Induced Bymentioning
confidence: 70%
“…Antibody to Toxoplasma tubulin (used at 1:1,000) was provided by David Sibley (Washington University, St. Louis, MO) to serve as a protein loading control. Mouse monoclonal antibody to phosphorylated H2AX was from Millipore (05-636) (12). Mouse monoclonal antibody to ATM kinase (2C1 (1A1); used at 1:2,000) was purchased from Abcam (ab78).…”
Section: Methodsmentioning
confidence: 99%
“…The replacement of canonical histones with histone variants can influence the nucleosome stability and chromatin patterns (95,123). Interestingly, in both Trypanosoma brucei and Toxoplasma gondii, H2A.Z interacts with H2Bv and is associated with active genes (31,99). In T. brucei, variant histones are used to mark boundaries of polycistronic transcription units, and nucleosomes containing two variant histones (H2A.Z and H2Bv) are highly enriched at the putative polymerase II transcription start sites (TSS) (137).…”
Section: Malaria Parasite Histones and "Histone Code"mentioning
confidence: 99%
“…H2AX has been shown to mediate DNA damage repair (12). In addition, it has been shown that H2AX transcription is upregulated in T. gondii in response to oxidative DNA damage (10). Previously, Singh et al (32) demonstrated that monensin caused significant oxidative stress and DNA fragmentation in rat testicular cells.…”
Section: Vol 55 2011mentioning
confidence: 99%